Effect of Once‐Weekly Exenatide on Clinical Outcomes According to Baseline Risk in Patients With Type 2 Diabetes Mellitus: Insights From the EXSCEL Trial. Issue 19 (2nd October 2018) - Mentz, Robert J.; Bethel, M. Angelyn; Merrill, Peter; Lokhnygina, Yuliya; Buse, John B.; Chan, Juliana C.; Felício, João S.; Goodman, Shaun G.; Choi, Jasmine; Gustavson, Stephanie M.; Iqbal, Nayyar; Lopes, Renato D.; et al.
Abstract : Background: In the EXSCEL (Exenatide Study of Cardiovascular Event Lowering), exenatide once‐weekly resulted in a nonsignificant reduction in major adverse cardiovascular events (MACEs) and a nominal 14% reduction in all‐cause mortality in 14 752 patients with type 2 diabetes mellitus (T2DM) with and without cardiovascular disease. Whether patients at increased risk for events experienced a comparatively greater treatment benefit with exenatide is unknown. Methods and Results: In the EXSCEL population, we created risk scores for MACEs and all‐cause mortality using step‐wise selection of baseline characteristics. A risk score was calculated for each patient, and a time‐to‐event model for each end point was developed including the risk score, treatment assignment, and risk‐treatment interaction. Interaction P values evaluating for a differential treatment effect by baseline risk were reported. Over a median follow‐up of 3.2 years (interquartile range, 2.2, 4.4), 1091 (7.4%) patients died and 1744 (11.8%) experienced a MACE. Independent predictors of MACEs and all‐cause mortality included age, sex, comorbidities (eg, previous cardiovascular event), body mass index, blood pressure, hemoglobin A1c, and estimated glomerular filtration rate. The all‐cause mortality and MACE risk models had modest discrimination with optimism‐corrected c‐indices of 0.73 and 0.71, respectively. No interaction was observed between treatment effect and risk profile for either end point (both interactions, P >0.1). Conclusions: Baseline characteristics (eg, age, previous cardiovascular events) and routine laboratory values (eg, hemoglobin A1c, estimated glomerular filtration rate) provided modest prognostic value for mortality and MACEs in a broad population of patients with type 2 diabetes mellitus. Exenatide's effects on mortality and MACEs were consistent across the spectrum of baseline risk. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01144338.